2023
DOI: 10.3389/fpubh.2023.1235276
|View full text |Cite
|
Sign up to set email alerts
|

The association between quality of life and subjective wellbeing among older adults based on canonical correlation analysis

Huanting Liu,
Qihui Gan,
Jianfeng Tan
et al.

Abstract: IntroductionThe study explored the relationship between subjective well-being and the quality of life among older adults. It highlights the importance of understanding how these factors are interconnected in the context of an aging population.MethodsDescriptive statistics were used to analyze the scores of general demographic characteristics, subjective wellbeing and quality of life. Simple correlation analysis and canonical correlation analysis were employed to analyze the relationship between subjective well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…The 1 st and 2 nd CVs cumulatively accounted for 99% of the relationship. The results were in keeping with some previous works on CCA (Adarkwah & Hirsh, 2020;Enginyurt et al, 2016;Mohammed-Abbas, 2015;Ojurongbe et al, 2018;Liu et al, 2023) The first canonical variate of this study showed that variables age, gender and location for demographic set were significant. Also the variables, body mass index (BMI) and treatment group (TG) for clinical set were significant.…”
Section: Discussionsupporting
confidence: 92%
“…The 1 st and 2 nd CVs cumulatively accounted for 99% of the relationship. The results were in keeping with some previous works on CCA (Adarkwah & Hirsh, 2020;Enginyurt et al, 2016;Mohammed-Abbas, 2015;Ojurongbe et al, 2018;Liu et al, 2023) The first canonical variate of this study showed that variables age, gender and location for demographic set were significant. Also the variables, body mass index (BMI) and treatment group (TG) for clinical set were significant.…”
Section: Discussionsupporting
confidence: 92%